2020
DOI: 10.1073/pnas.1821683117
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of CO to acetaldehyde with CuAg electrocatalysts

Abstract: Electrochemical CO reduction can serve as a sequential step in the transformation of CO2into multicarbon fuels and chemicals. In this study, we provide insights on how to steer selectivity for CO reduction almost exclusively toward a single multicarbon oxygenate by carefully controlling the catalyst composition and its surrounding reaction conditions. Under alkaline reaction conditions, we demonstrate that planar CuAg electrodes can reduce CO to acetaldehyde with over 50% Faradaic efficiency and over 90% selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 66 publications
1
75
0
1
Order By: Relevance
“…DFT calculations of our previous study showed that an expanded Cu lattice increases the binding energies for the intermediates of CO 2 RR (e.g., *CO on Cu) [9c] . Additionally, Ag incorporation in Cu weakens the binding energies of the reduced aldehyde intermediates and inhibits their further reduction to ethanol and 1‐propanol as demonstrated in a recent DFT study [22] . However, the structural analysis of the catalysts showed that the surface partially consists of Cu/Ag areas, which also leads to the formation of ethanol and 1‐propanol at the Cu sites, since they are expected to have higher binding energies for the oxygenated intermediates as compared to the Ag–Cu mixed regions.…”
Section: Resultsmentioning
confidence: 69%
“…DFT calculations of our previous study showed that an expanded Cu lattice increases the binding energies for the intermediates of CO 2 RR (e.g., *CO on Cu) [9c] . Additionally, Ag incorporation in Cu weakens the binding energies of the reduced aldehyde intermediates and inhibits their further reduction to ethanol and 1‐propanol as demonstrated in a recent DFT study [22] . However, the structural analysis of the catalysts showed that the surface partially consists of Cu/Ag areas, which also leads to the formation of ethanol and 1‐propanol at the Cu sites, since they are expected to have higher binding energies for the oxygenated intermediates as compared to the Ag–Cu mixed regions.…”
Section: Resultsmentioning
confidence: 69%
“…Generally, CO 2 can be rst reduced into CO through the *COOH pathway, 28 and the adsorbed CO is regarded as the common intermediate for the C 2+ products in CO 2 RR. 66 In this condition, four potential reaction pathways are taken into account in the C-C coupling step and all of them are generated from the vital intermediate *CO (Fig. S28-S33 †).…”
Section: Resultsmentioning
confidence: 99%
“…*CO auf Cu) erhöht [9c] . Außerdem schwächt die Einführung von Ag in Cu die Bindungsenergien der reduzierten Aldehyd‐Intermediate und hemmt deren weitere Reduktion zu Ethanol und 1‐Propanol, wie eine neuen DFT‐Studie dargelegte [22] . Trotzdem zeigte die genaue strukturelle Analyse der Katalysatoren, dass die Oberfläche teilweise auch aus Cu/Ag‐Flächen besteht.…”
Section: Ergebnisse Und Diskussionunclassified